Postoperative Airway Obstruction by a Bone Fragment - Patrick Schober; K. Hakki Karagozoglu; Stephan A. Loer; Lothar A. Schwarte (Case Reports in Anesthesiology)
Postoperative airway obstructions are potentially life-threatening complications. These obstructions may be classified as functional (sagging tongue, laryngospasm, or bronchospasm), pathoanatomical (airway swelling or hematoma within the airways), or foreign body-related. Various cases of airway obstruction by foreign bodies have previously been reported, for example, by broken teeth or damaged airway instruments. Here we present the exceptional case of a postoperative airway obstruction due to a large fragment of the patient’s maxillary bone, left accidentally in situ after transoral surgical tumor resection. Concerning this type of airway obstruction, we discuss possible causes, diagnosis, and treatment options. Although it is an exceptional case after surgery, clinicians should be aware of this potentially life-threatening complication. In summary, this case demonstrates that the differential diagnosis of postoperative airway obstructions should include foreign bodies derived from surgery, including tissue and bone fragments.